Model Pembelajaran Bahasa Arab Di Pondok Pesantren Salaf Kediri Dan Kontribusinya Terhadap Kemampuan Membaca Teks Berbahasa Arab Bagi Santri - Nurul Hanani (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2015)
The aim of this study is to examine how the teaching of Arabic at Pondok Pesantren Salaf is implemented such that it is able to improve skill in reading Arabic texts. This study is then expected to propose a theory of teaching Arabic that is effective particularly in the teaching of reading. This is a qualitative study employs pondok pesantren that is assumed as teaching Arabic using classic books (Salafiyah). Case study is used in order that the researcher can uncover this phenomenon completely and comprehensively in the form of analytic description to answer a number of research questions, so that this study is able to this explain the system of Arabic education and teaching at those pesantren. This study is conducted in three large pesantren in Kediri, those are Pondok Pesantren Al-Falah Ploso Mojo Kediri, Pondok Pesantren Hidayatul Mubtadi’in Lirboyo Kota Kediri, and Pondok Pesantren Darus Salam Sumbersari Kepung Kediri. These three pesantren is selected based on the assumtion that they represent all pondok pesantren in Kediri. The present study concludes that: (1) The teaching of Arabic at Pondok Pesantren salaf in Kediri commonly use traditional system of Arabic teaching, in the forms of bandongan (the teacher is reading aloud the book and explaining the grammar as weel as the meaning, and the students are seriously listening), sorogan (the students are reading aloud the book and explaining both the grammar and the meaning, and the teacher is listening and giving some necessary corrections on both the grammar and the meaning), and memorizing. Although these three pesantren employ approximately the same methods, some differences are found. Pondok Lirboyo applies four classic methods (bandongan, sorogan, memorization and discussion), Pondok Al-Falah Ploso applies the system of salaf education and student centered teaching, that emphazies on the autonomy and activeness of the students, and Pondok Sumbersari pplies dual system of teaching, i.e. traditional pondok sistem of education dan formal schools; (2) The contribution of this model of teaching Arabic at pondok pesantren to improve ability in reading Arabic resources for santri is very significant. This is because the methods applied are very easy to understand and realize, besides the traditional pesantren does not stick on formal education but provide alternative teachings in order to improve students’ ability in reading Arabic classic resources.